Utilization Of Coffee Grounds into Bio-Briquettes Using Various Types of Adhesives with Carbonization Method - Luh Putu Irma Sridewi Yogeswari; Nispi Yuliani; Belva Chiquita; Alfiana Adhitasari; Unung Leoanggraini (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Coffee is one of the most widely produced and consumed agricultural commodities in Indonesia, with production rates increasing each year. This growing demand results in an increasing volume of spent coffee grounds, which are typically discarded as waste. One sustainable approach to managing this waste is by converting it into bio-briquettes, a form of solid fuel. This study aims to evaluate the physicochemical characteristics of coffee ground-based briquettes using different types of adhesives in accordance with the Indonesian National Standard (SNI 01-6235-2000) and to determine which adhesive yields the highest briquette quality. Three types of adhesives were tested: tapioca starch, sago starch, and polyvinyl alcohol (PVA), each mixed with carbonized coffee grounds in a 1:10 ratio. The briquettes were analyzed based on key performance indicators, including moisture content, ash content, volatile matter, density, fixed carbon, and calorific value. The carbonization process was applied prior to briquette formation to improve fuel quality. The results showed that the briquette using PVA as an adhesive exhibited the best overall performance, with a density of 0.449 g/cm³, ash content of 4.360%, moisture content of 1.480%, volatile matter of 33.974%, fixed carbon of 59.743%, and a calorific value of 6.861 cal/g. These findings suggest that PVA-based briquettes offer promising potential in reducing biomass waste and supporting the development of renewable energy in Indonesia.